Avaliação in silico, in vitro e in vivo de naftoquinonas naturais e sintéticas visando a seleção de candidatos a desenvolvimento de antimaláricos. - Maria Fernanda Alves do Nascimento (2020)
Malaria is a human parasitic disease with high impact on public health in tropical and sub-tropical areas, contributing considerably to mortality in these regions. Plasmodium falciparum and P. vivax are the main ethiological agents of human malaria and are transmitted by infected females of Anopheles mosquitoes. Despite considerable progress in malaria control interventions over the past 15 years, case and mortality figures are still unaffordable for a treatable disease, what is related to several factors such as increasing resistance to existing antimalarial drugs and limited effectiveness of the most advanced vaccine in development. There are many reports on antimalarial substances, including natural and synthetic naphthoquinones, most of which are still preliminary results, and there are few publications on preclinical studies for the evaluation of different classes of chemical substances with proven in vitro and / or in vivo activity what have motivated the present work. A total of 42 naphthoquinones were evaluated, 39 are synthetic and 3 are natural products. The assayed naphthoquinones disclose different structural characteristics such as 2hydroxynaptoquinones / HNQs (1a-1h), ortho-FNQs (2a-2h), para-FNQs (3a-3h), AMQs (4a-4d), and mefloquine salts combined with HNQs or lapachol (5a-5i). The following steps were carried out: 1- In silico evaluation of ADME and toxicological properties by the PreADMET program; 2- Evaluation of in vitro antiplasmodial activity and cytotoxicity in different cell types, HepG2 cells (human Hepatoma), LLC-PK1 (epithelial cells of the proximal tubule pig kidney), A549 (human lung adenocarcinoma), Neuro-2A (mouse neuroblastoma) and MRC-5 (human fetal lung fibroblast); 3- OECD 129; 4- Acute oral toxicity - OECD 423 and 5 - Blood schizonticidal test in mice. The results of the in silico methodologies pointed to HNQs and AMQs as those with the most favorable properties among all the 42 substances. Regarding the IS of all substances, the mefloquine salts combined with HNQs and lapachol were the ones with the highest values (0.43 to 32.73). However, the salts were very cytotoxic to renal cells, with CC50 values between 5.59-21.87µM. The in vitro cytotoxicity test, substances with highest CC50 values were selected for the final tests. These results allowed the selection of 3 out of the 42 naphthoquinones (1a, 1g, and lapachol) for the OECD 129 tests, acute oral toxicity in vivo (OECD 423) by extrapolating the results in the OECD 129, and in the blood schizonticidal test in mice. Lapachol, one of the 3 naphthoquinones evaluated was lapachol, an active substance occurring in several species of the genus Handroanthus (synon. Tabebuia), of the Bignoniaceae family that was used in malaria therapeutics in former times. The initial dose predicted, by the OECD 129, for the oral toxicity test was 300mg/kg and it was firstly assayed and afterwards a dosis of 2000mg/kg was administered. The three substances (1a, 1g, and lapachol) did not show any serious signs of toxicity in any of the tested doses (300 and 2000mg/ kg). However, in the in vivo blood schizonticidal test, no reduction of parasitemia was observed in the mices, in comparison with the untreated controls. On the basis of the present results, a possibility to be still considered for these three naphthoquinones would be the development of special pharmaceutical formulations which, by their particular properties, could compensate the low bioavalialibility of these compounds that could be a cause of their inactivity in the antmalarial in vivo assay.